(untitled) (Indian Journal of Animal Production and Management, 2024)
The study was conducted at Goat Research Project, Vasantrao Naik Marathwada Agricultural University, Parbhani. Eighteen Osmanabadi kids were selected and were allocated to three experimental groups based on concentrate feed replacement with Moringa oleifera Leaf Powder (MOLP) i.e., T0 (0%), T1(10%) and T2 (20%). The study lasted for 90 days in intensive rearing system. The averages for weekly body weight (Kg) of kids fed with MOLP for group T0, T1 and T2 at the end of 13th week were 14.40±0.36, 14.86±0.47 and 16.40±0.45 kg, respectively depicting significantly higher values for T2 group than Ti group whereas non-significant difference between T0 and T1 group. The weekly body weight gain was 0.39±0.01, 0.40±0.01 and 0.54± 0.01 kg, respectively while the daily weight gain observed were 55.95±2.07, 56.90±1.31 and 76.64±1.67 gm respectively with highly significant difference between T2 group as compared to T1 and T0 group. The mean values for weekly and daily feed intake for groups T0, T1 and T2 were 70.95±0.43 and 10.14±0.06, 71.38±0.41 and 10.20±0.06, and 70.40±0.06, and 10.06±0.01 kg, respectively. The feed conversion efficiency (FCR) was significantly (P<0.01) better in T2 (6.49±0.00) as compared to T1 (8.82±0.03) and T0 (8.93±0.04). There was higher growth performance of Osmanabadi kids in T2 treatment group as compared to T1 and T0 groups. It can be concluded that the concentrate feed can be replaced up to 20% by Moringa oleifera leaf powder in Osmanabadi kids reared intensively without any adverse effect on growth.